On the existence of periodic solutions for Liénard type φ-Laplacian equation - Yang, Congmin; Wang, Zaihong (Topological Methods in Nonlinear Analysis, 2023)
In this paper, we study the existence of periodic solutions for a Liénard type φ-Laplacian equation (φ(x’))’+f(x)x’+g(x)=p(t). We prove a continuation lemma and use it to prove the existence of periodic solutions for above equation when g or G (the primitive of g) satisfies some one-sided or bilateral growth conditions and F (the primitive of f) satisfies sublinear condition.